2016
DOI: 10.18088/ejbmr.2.2.2016.pp30-36
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of cerebral acupuncture affects neuronal cell apoptosis via BrdU and Nestin in hypoxic-ischemic brain-damaged immature rats

Abstract: In this study, the effects of scalp acupuncture on the number of apoptotic cells and apoptotic indexes were deterrmined in rats with intrauterine hypoxic-ischemic brain damage(HIBD), and the inhibitory mechanism of mitochondrial pathway, mediated apoptosis in the repair of brain ischemia and hypoxia was examined. A clip was applied to the uterine artery for 5 min before a cesarean section was performed in a rat model. The rats were divided into normal group (n = 24), model group (n = 24), and acupuncture group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Additionally, limb ischemia–reperfusion research showed that electroacupuncture (EA) has neuroprotective possible mediated, at least in part, by decrease of oxidative stress and inhibition of microglial activation 17 . In addition, various studies have shown that acupuncture restores apoptosis in different disease conditions 18, 19, 20. Many studies have indicated that acupuncture stimulation is effective for depression and that its underlying mechanism involves mitigating apoptosis 21, 22.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, limb ischemia–reperfusion research showed that electroacupuncture (EA) has neuroprotective possible mediated, at least in part, by decrease of oxidative stress and inhibition of microglial activation 17 . In addition, various studies have shown that acupuncture restores apoptosis in different disease conditions 18, 19, 20. Many studies have indicated that acupuncture stimulation is effective for depression and that its underlying mechanism involves mitigating apoptosis 21, 22.…”
Section: Introductionmentioning
confidence: 99%